Raking Effects on Aggregate Densification and Channelling in Thickening - Xu Zhou; Hong-jiang Wang; Hua-zhe Jiao; Liu-hua Yang (Advances in Materials Science and Engineering)
Thickening performance is greatly influenced by aggregate densification and channelling development; however, the microstructures of aggregates and channelling are unable to directly observe because of high turbidity mud bed during thickening. Computed tomography scan imaging technique has been introduced to investigate the effects of aggregate densification and channelling in the mud bed samples during unclassified tailings thickening. The samples were prepared through deep-freezing and freeze-drying techniques, immediately after sampling from the operation of a pilot thickener. Based on the information of void ratio, pore-size distribution, and permeability, obtained from 3D reconstruction images of the aggregates structure, aggregate densification and channelling development have been characterized. Channelling patterns have been classified by the size and shape of the connection throat of the pore between aggregates. As the aggregate structure broke and densified, the void ratio and pore size of the mud bed were decreased. Thickening performance enhancement was predicted based on solid flux and permeability of mud bed, and the result indicated raking on aggregate densification and channelling apparently improves the unclassified tailings dewatering extent.